(untitled) (Academia Journal of Medicine, 2026)
Aim: To comparatively evaluate the onset time and efficacy of buffered 2% lidocaine with 1:100,000 adrenaline and non-buffered 2% lidocaine with 1:100,000 adrenaline in patients undergoing dental extraction. Materials and Methods: This randomized, single-blind clinical study was conducted on 40 patients indicated for simple dental extraction. The patients were randomly divided into two groups (n = 20 each). Group I received non-buffered 2% lidocaine with 1:100,000 adrenaline, while Group II received buffered 2% lidocaine with 1:100,000 adrenaline. The buffered solution was prepared by adding 8.4% sodium bicarbonate to the anesthetic solution immediately before administration. The onset time of anesthesia was recorded using a stopwatch from completion of injection to the first subjective sign of numbness. Pain during injection and pain during extraction were assessed using a Visual Analog Scale (VAS). The need for supplementary anesthesia was also recorded. Statistical analysis was performed using the independent t-test and Chi-square test, with the level of significance set at p < 0.05. Results: The buffered lidocaine group demonstrated a significantly faster onset of anesthesia compared to the non-buffered group (p < 0.05). Pain scores during injection and during extraction were significantly lower in the buffered group. Additionally, fewer patients in the buffered group required supplementary anesthesia. Conclusion: Buffered 2% lidocaine with 1:100,000 adrenaline provides faster onset and improved anesthetic efficacy with reduced pain perception compared to non-buffered lidocaine during dental extraction. Its use may enhance patient comfort and clinical efficiency in routine dental practice.